Banking capitalization strategy and its impact on enhancing its digital transformations - Mustafa Hashim Hasan; Nagham Dayekh Abid-Ali (Technium Business and Management, 2023)
The study addressed the issue of the banking capitalization strategy with its indicators (retained profits, issuance of new shares, and reserves) and its impact on enhancing its digital transformations with its indicators (the electronic clearing system and the gross real-time settlement system). The study sought to identify the nature of the banking capitalization strategy and provide a theoretical and philosophical framework based on intellectual qualification. And make a modest contribution regarding the variables and dimensions of the study. The study sample was chosen at the Central Bank of Iraq due to the major role it plays in the country’s economy, and through the financial reports published on the official website of the Central Bank for the period from (2011-2022). The researcher also used a set of statistical methods (SPSSV25, Excel V). 10, Eviews v.12) in order to process data and information. The study also tested a set of main and sub-hypotheses regarding the influence relationships between the variables of the study.